2002
DOI: 10.1124/jpet.302.1.174
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Serotonin Reuptake Inhibitor Citalopram Induces the Storage of Serotonin in Catecholaminergic Terminals

Abstract: We investigated whether selective inhibition of serotonin (5-hydroxytryptamine; 5-HT) transporter with citalopram leads to accumulation of 5-HT in catecholaminergic neurons. In the rabbit olfactory tubercle, citalopram (1-10 M) inhibited [3 H]5-HT uptake; however, the maximal degree of inhibition achieved was 70%. Addition of nomifensine (1-10 M) was required for complete inhibition of Despite their lower affinity for serotonin (5-hydroxytryptamine; 5-HT), there is experimental evidence to suggest that catecho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…These results show that 5,7-DHT can also damage DA, at least when injected in doses of 25-50 g into the ventral striatum, and this effect can be abolished when inhibiting DA transporters by nomifensine. On the other hand, nomifensine treatment diminished 5HT damage in a dose-dependent way, possible since nomifensine might also partially inhibit 5HT transporters (Suarez-Roca and Cubeddu, 2002). To limit this unwanted 5HT effect, we decided to use the lower dose of nomifensine in the final experiment.…”
Section: Discussionmentioning
confidence: 98%
“…These results show that 5,7-DHT can also damage DA, at least when injected in doses of 25-50 g into the ventral striatum, and this effect can be abolished when inhibiting DA transporters by nomifensine. On the other hand, nomifensine treatment diminished 5HT damage in a dose-dependent way, possible since nomifensine might also partially inhibit 5HT transporters (Suarez-Roca and Cubeddu, 2002). To limit this unwanted 5HT effect, we decided to use the lower dose of nomifensine in the final experiment.…”
Section: Discussionmentioning
confidence: 98%
“…First, the increased values for K m and V max in striatal versus hippocampal synaptosomes appear to be due to significant 5-HT uptake via DAT. This is not surprising considering that striatal neurons establish synaptic contact with both DAT-and SERTexpressing terminals (Graybiel and Ragsdale, 1983) and that 5-HT can be transported as a substrate for DAT and modulate DAT activity (Stamford et al, 1990, Jacocks and Cox, 1992, Jackson and Wightman, 1995, De Deurwaerdere et al, 1996, Suarez-Roca and Cubeddu, 2002, Zhou et al, 2002, Riddle et al, 2003, Callaghan et al, 2005. Second, the concentration of fluoxetine (10 μM) used for defining nonspecific [ 3 H]5-HT uptake in striatal synaptosomes appears to have inhibited DAT.…”
Section: Discussionmentioning
confidence: 98%
“…In another study, Zhou and colleagues (2005) showed that striatal dopaminergic terminals will take up 5-HT and subsequently release both 5-HT and DA when SERT is inhibited by a serotonin specific reuptake inhibitor (SSRI) and extracelluar levels of 5-HT are elevated. In addition, 5-HT was found to be taken up, stored, and subsequently released by catecholaminergic neurons in rabbit olfactory tubercle under conditions in which serotonin transporter (SERT) activity was inhibited by the SSRI, citalopram (Suarez-Roca and Cubeddu, 2002). Riddle et al (2003) extended these findings by showing that ceramide, an agent known to alter the phosphorylation state of transporter proteins, increases 5-HT uptake and reduces DA uptake through DAT.…”
Section: Introductionmentioning
confidence: 93%
“…However, such an ‘intimate’ interaction as the one described by Zhou et al . had not been directly demonstrated before, despite some preliminary suggestive evidence ( Stamford et al ., 1990 ; Suarez‐Roca & Cubeddu, 2002 ).…”
mentioning
confidence: 84%